Indonesian Culture Learning Application based on Android - Alexander Setiawan; Andreas Handojo; Rendra Hadi (Institute of Advanced Engineering and Science, 2017)
Indonesia is a country that has a wealth of diverse cultures spread from Sabang to Merauke. Even though the government has included a lesson about Indonesian culture in terms of some subjects such as Art and Culture, but there are still many people including some students who do not know the forms and names of the tribes, traditional houses, traditional clothing, folk songs, traditional foods, local weapons, and musical instruments regions in Indonesia. Therefore, a learning application is created that utilizes mobile learning technology. Through the use of mobile learning, user can access learning content without any borders so that it can be accessed at any time so that it can be accessed at any time with interesting illustration. Indonesia National Culture Application is made useful to help users in learning the introduction of Indonesian culture that provides the knowledge with illustrations in the form of images, audio, text and video. This application also can be functioned to learn, answer quiz, to view a gallery of images and video and to do puzzle games. The achieved result is an application that can provide knowledge to the users so they can know the culture in Indonesia through the illustrations provided well.